1978
DOI: 10.3177/jnsv.24.351
|View full text |Cite
|
Sign up to set email alerts
|

Active transport of thiamine by freshly isolated rat hepatocytes.

Abstract: SummaryRat hepatocytes were freshly prepared from adult animals using the collagenase-perfusion technique. The hepatic transport of thiamine was studied in isolated liver cells. The process was found to be saturable with an apparent Kt of 0.31mM and a Vmax of 0.7 umoles/ml intracellular fluid/5 minutes. However, at higher substrate concentrations, the process proceeded in a linear fashion. Both pyrithiamine and oxythiamine were inhibitory on the hepatic uptake of thiamine, the latter showed much weaker activit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

1979
1979
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(6 citation statements)
references
References 26 publications
1
5
0
Order By: Relevance
“…Our finding that thiamin transport in the heart is energydependent is in good agreement with the properties of thiamin uptake in other tissues, such as human retinal pigment cells (Subramanian et al 2007) or hepatocytes (Chen 1978). Taking into account our finding that thiamin transport is energy-dependent, this could explain the reduction of thiamin transport across the cellular membrane of cardiac cells of chronically alcoholic animals.…”
Section: Discussionsupporting
confidence: 79%
“…Our finding that thiamin transport in the heart is energydependent is in good agreement with the properties of thiamin uptake in other tissues, such as human retinal pigment cells (Subramanian et al 2007) or hepatocytes (Chen 1978). Taking into account our finding that thiamin transport is energy-dependent, this could explain the reduction of thiamin transport across the cellular membrane of cardiac cells of chronically alcoholic animals.…”
Section: Discussionsupporting
confidence: 79%
“…When the intestinal concentration of T + is <2 μM, however, T + is actively transported by OCTs and ALPs . Recent studies show, however, that both active transport and passive transport of T + occur simultaneously in the same tissues and organs. , For other forms of thiamin, TPP, and TTP (which are normally not available extracellularly , ), the transfer across membranes is conducted after conversion back to the TMP and T + forms. , Once delivered to the cytosol, thiamin is metabolized to all three forms of thiamin (Figure ) in the tissues and organs, as well as the cationic form , (Figure ).…”
Section: Thiamin Transportmentioning
confidence: 99%
“…The underlying mechanism of transplacental transport of thiamine has been investigated using in vitro perfusion techniques (3,4) as well as isolated placental brush border membrane vesicles (5). Thiamine transport has also been functionally characterized in other tissues/ cells such as intestine (6 -9), erythrocytes (10), hepatocytes (11), and neuroblastoma cells (12). These studies have shown that the transport of thiamine is a carrier-mediated, energydependent process.…”
mentioning
confidence: 99%